A species checklist of wild orchids in selected sites in Kadamaian, Kota Belud, Sabah - Besi, Edward Entalai; Nikong, Dome; Mat Esa, Mohd Ikhwanuddin; Mus, Ahmad Asnawi; Nelson, Heira Vanessa; Mohamad, Nurul Najwa; Ombokou, Roslin; Rusdi, Nor Azizun; David, Devina; Abdul Aziz, Zaleha; Go, Rusea (Universiti Malaysia Sabah, 2021)
A brief orchid diversity study was conducted from 14th to 19th October 2019 in Kadamaian, located northwest of Kinabalu area, through a scientific geographic expedition. A convenience sampling method was employed with only the flowering individuals collected and preserved as herbarium specimens. A total of 58 species and 32 genera were identified during the field visits to the Mount Nopungguk, Melangkap Noriou, Ulu Sungai Melawa, and basecamp site. The finding comprises of 43 epiphytes, 13 terrestrials, and two mycoheterotrophs. Appendicula congesta, Bulbophyllum disjunctum, Dendrobium kiauense, and Goodyera rostellata are species endemic to Borneo found during the expedition along with Crepidium multiflorum, a hyper-endemic species to Kinabalu area. Several rare species which narrowly distributed to primary forest habitat were discovered, including jewel orchids; Cystorchis variegata var. variegata and Anoectochilus geniculatus, and two mycoheterotrophs; Aphyllorchis pallida and Lecanorchis multiflora var. multiflora.